Propuesta Para La Implementación De Un Sistema De Gestión Y Control De Inventarios En La Empresa “Fscr Ingeniería Sas” En La Ciudad De Santa Marta Magdalena (2024)
FSCR INGENIERÍA S.A.S., a leading company in the telecommunications sector, identified the need to optimize its inventory management and control processes to improve operational efficiency and maintain a high level of service to its customers. In response to this need, the company decided to undertake a project to implement a comprehensive inventory management and control system. The project began with an exhaustive analysis of the company's current practices regarding inventory management, identifying areas for improvement and opportunities to optimize processes.This solution, called "OWS (Operation Web Services), was developed by the company AUTIN OWS, a leader in technological solutions for inventory control. A key aspect of the project was the adoption of the inventory control system known as "kardex", which allows keeping a detailed and updated record of the input and output movements of materials, as well as stock balances. To evaluate the performance of the new system, key performance indicators (KPIs) were established focused on management efficiency. of orders, the value of available inventory, and product availability and coverage.